An approach to long range production and development planning with application to the Kiruna Mine, Sweden - Almgren, Torgny (Luleå tekniska universitet, 1994)
The mining industry is increasingly oriented towards large scale mining and the planning concept of "Just in Time", which means activities starting and ending as late as possible without jeopardising production. The buffers, consisting of production blocks and development ahead of production, are then minimi. This, however, leads to a larger dependency on the quality of the output from the production systems. The Kiruna mine, Sweden, is a large scale mine and has a number of potential ore blocks with a content that varies in quality (Fe, P, K) and in quantity (ore tonnage). Ore production is restricted by operative and block sequencing constraints as well as by production requirements. A computerized planning model, based on operations research (multi period scheduling) has been developed to meet future demands on ore qualities and quantities. The model uses long range objectives, but can satisfy temporary short range demands without jeopardising the long range goals. A sub-optimal plan, made using the model, has been compared with a truly optimal plan. It is shown that, due to the unreliable information concerning the ore, the sub-optimal plan performs as well as the optimal one. The simulation process that was developed for this comparison is also used to estimate the need for production buffer blocks. Another buffer planning model is developed to determine when development work should take place in order to minimize the risk of additional costs, caused by an inability to start production on time. This algorithm considers the uncertainties in activity durations and is based on a Monte Carlo simulation using project networks and estimates the optimum development buffer. Godkänd; 1994; 20070429 (ysko)